KEBIJAKAN DAN MANAJEMEN PENDIDIKAN MERDEKA BELAJAR-KAMPUS MERDEKA: PERSOALAN DAN TANTANGAN - Hastangka Hastangka; Yayuk Hidayah (Jurnal Muara Pendidikan, 2023)
The concept of "Kampus Merdeka" (Independent Campus) and "Merdeka Belajar" (Independent Learning) has gained attention in the dynamics and discourse of education policy and management. The concept of independent campus and independent learning seems to be a national education jargon that is perceived as "fantastic", "interesting", and "buzzworthy". The purpose of this article is to examine the concept of independent campus and independent learning policy and management. The methodology used in this article is qualitative research, with documentation technique to identify discourse from books, papers, articles, magazines, journals, or other related information on independent campus and independent learning policy and management. The data analysis used in this article is descriptive analysis. The research results indicate that the fundamental problems in the implementation of the independent campus and independent learning policy and management are in the aspects of implementation, governance, and higher education management in building an ecosystem of knowledge and student mobility between study programs, faculties, and universities. The research also shows that the main challenges of implementing independent campus and independent learning in Indonesia are: 1. Knowledge about the program, 2. Policy, 3. Management, 4. Budget allocation. Moreover, the policy aspect has not yet shown a comprehensive and integrated policy to make independent campus and independent learning programs an integral part of the education system in universities. This article is expected to provide reflection on improving the implementation of independent campus and independent learning policy that has been running, so that it can be ideal for the education world in Indonesia.